1989
DOI: 10.1515/znc-1989-5-610
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Isotope Fractionation by Autotrophic Bacteria with Three Different C02 Fixation Pathways

Abstract: D edicated to Professor A chim Trebst on the occasion o f his 60th birthdayCarbon Isotope Fractionation. Autotrophy. A cetyl-C oA Pathway, Reductive Citric Acid Cycle, Calvin Cycle Carbon isotope fractionation during autotrophic growth o f different bacteria which possess different autotrophic C 0 2 fixation pathways has been studied. 13C /l2C -R atios in the cell carbon of the follow ing bacteria were determined ( C 0 2 fixation pathway suggested or proven in paren theses): A lkaligenes eutrophus (reductive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
92
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 13 publications
12
92
1
Order By: Relevance
“…Because a fractionation of ϳϪ10.7‰ exists between dissolved CO 2 and dissolved inorganic carbon (dominated by bicarbonate) at the in situ temperature (ϳ10°C) (35), the actual isotope compositions of the respired CO 2 can be as low as Ϫ38.2‰. Second, if Beggiatoa used this light CO 2 for chemoautotrophic growth, the biomass should have had a ␦ 13 C value close to or below Ϫ60‰, given the typical fractionations of 20 to 26‰ between biomass and CO 2 for autotrophs using the Calvin cycle (30,48,51,59). Our measured ␦ 13 C value of biomass (Ϫ28.6‰) was significantly higher.…”
Section: Resultsmentioning
confidence: 99%
“…Because a fractionation of ϳϪ10.7‰ exists between dissolved CO 2 and dissolved inorganic carbon (dominated by bicarbonate) at the in situ temperature (ϳ10°C) (35), the actual isotope compositions of the respired CO 2 can be as low as Ϫ38.2‰. Second, if Beggiatoa used this light CO 2 for chemoautotrophic growth, the biomass should have had a ␦ 13 C value close to or below Ϫ60‰, given the typical fractionations of 20 to 26‰ between biomass and CO 2 for autotrophs using the Calvin cycle (30,48,51,59). Our measured ␦ 13 C value of biomass (Ϫ28.6‰) was significantly higher.…”
Section: Resultsmentioning
confidence: 99%
“…Most interestingly, this is also observed in the dark, which excludes photosynthetically active organisms like algae, so that heterotrophic CO 2 fixation is suggested (Miltner et al 2005a). Several metabolic pathways of microorganisms are known for this heterotrophic carbon uptake (Preuss et al 1989;Berg et al 2007) and might be, in consequence, a missing process for carbon uptake. For soils on sedimentary substrates, carbon stored in rocks, i.e., kerogen and bitumen (Engel and Macko 1993), and (Kramer and Gleixner 2006) carbon found in coal and char is used for growth by soil microorganisms (Petsch et al 2001;Steinbeiss et al 2009;Seifert et al 2011).…”
Section: Role Of Soil Microorganismsmentioning
confidence: 89%
“…Consequently, their ␦ 13 C could be Ϫ26‰ or lower in the Cariaco, where the DIC is Ϫ1‰ to Ϫ2‰ (Fry et al 1991). Preuß et al (1989) have reported even greater 13 C fractionation for non-sulfur-oxidizing autotrophic bacteria (⌬␦ 13 C of Ϫ26.1‰ to Ϫ39.7‰, depending on the DIC fixation pathway). Although isotopic signatures of anaerobic, chemolithotrophic bacteria are unknown, it seems likely that chemoautotrophic production in the RTZ will be isotopically light and that the isotopic signature of bacterivorous organisms will be even more depleted in 13 C and 15 N (Ruby et al 1987).…”
mentioning
confidence: 99%